Vulnerability in a mobile world - Forbes-Mewett, Helen (Emerald Publishing Limited, 2019)
Populations across the world are becoming increasingly mobile for many different reasons. Some are searching for a better and safer life, others migrate for economic or environmental purposes, education, or identity formation. While mobility may bring better life-chances, this book shows that for some it means experiencing vulnerability. Vulnerability in a Mobile World considers the notion of vulnerability from various standpoints including intercultural relationships, homelessness, urbanisation, refugee and asylum seekers, and the use of YouTube by young girls. The diversity of the circumstances and characteristics of the vulnerable enable this book to uniquely show just how broad the notion of vulnerability can be. Presenting an international perspective to social problems in various settings, the chapters are brought together in a coherent argument that shows vulnerability has many forms and is often associated with mobile populations. Vulnerability in a Mobile World is based on a collection of studies by new and emerging scholars focussing on the impacts of migration and mobility in contemporary contexts. Within this framework, each chapter presents new findings that provides poignant examples of vulnerability involving diverse populations, geographical locations and circumstances.